Investigation of noise threats and their impact on hearing in selected schools – a pilot study - Kotus, Joseph; Kostek, Bożena (Archives of Acoustics, 2006)
Noise measurements conducted in selected schools in Gdańsk area are presented in this paper.The main aim of this research was to determine noise threats at schools. Some objectivemeasurements of the acoustic climate were performed employing a noise monitoring stationengineered at the Multimedia System Department, Gdańsk University of Technology. Simultaneously,subjective noise annoyance examinations were carried out among pupils in chosenschools. The survey includes a noise analysis in places of residence, music preferences andpreliminary hearing tests results taken after the exposure to noise during breaks. Hearing testsemploying a distortion product otoacoustic emission (DPOAE) method, have been performedtwice – before and after the exposure to noise. The noise dose analysis based on average timespent by a pupil at school is also presented. The obtained results reveal that an unfavorablenoise climate occurred in surveyed schools. This was also confirmed by the results of thesubjective examinations. The conducted hearing tests did not reveal essential changes in thecochlea activity of examined pupils. This means that the noise during breaks and physicalexercises did not constitute a risk to their hearing system. However, it may be considered asan essential source of annoyance.